DINAMIKA KEPADATAN DAN DISTRIBUSI VERTIKAL ARTHROPODA TANAH PADA KAWASAN HUTAN TANAMAN INDUSTRI (Jurnal Pilar Sains, 2008)
Have been conducted a research to find out the Dynamic of the Density and VertikalDistribution of soil Arthropods on the deep of the Forest Industry Cultivation Area. Theobservation point sampling determining was conducted bassed on sampling randomized purposivethe is on the HTI area 0, 2, 4, and 6 year of plant age with each of the area 100x100m widht. Oneach station is determined by 3 quatation randomized with 3 times removal of land sampel. Thephysic-chemistry parameter that had been observed including pH, temperature, soil water contentand soil of organic content, mean while the biology parameter including density and index ofdistribution. The result showed the individu that had been found that is 11 ordo, 19 species with880 individu total. The dominant of Arthropods group is from the collembola species and thelowest is Araneae. The Dynamic highest density are on the 6 year of plant age 0,170 cm 3/speciesand the lowest on 0 year 0,054 cm3/species where as the number of density is higher on the Astratum rather than B stratum and C stratum. Vertical distribution showed only on the 0 year isdistributed be in cluster otherwise on the 2, 4, and 6 year age are distributed be spread evenly.Key word : Arthropods, Density,Distribution vertical, Forest Industry Cultivation .